2014
DOI: 10.1007/s00190-014-0745-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of individual and combined zenith tropospheric delay estimations during CONT08 campaign

Abstract: CONT campaigns are 2-week campaigns of continuous VLBI observations. The IERS working group on combination at the observation level uses these campaigns to study such combinations. In this work, combinations of DORIS, GPS, SLR, and VLBI technique measurements are studied during CONT08. We present different results concerning the use of common zenith tropospheric delay (ZTD) during the combination. We compare the ZTD obtained separately using each individual technique data processing, the combined ZTD, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…In general, these parameters have an excellent agreement of better than 1 cm in RMS and are consistent with numerical weather models and other meteorological measurements (Pollet et al, 2014). Teke et al (2013) showed ZTD and gradients during CONT02 to CONT11 derived from observations of GNSS, VLBI, DORIS, water vapor radiometers (WVR), and numerical weather model.…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…In general, these parameters have an excellent agreement of better than 1 cm in RMS and are consistent with numerical weather models and other meteorological measurements (Pollet et al, 2014). Teke et al (2013) showed ZTD and gradients during CONT02 to CONT11 derived from observations of GNSS, VLBI, DORIS, water vapor radiometers (WVR), and numerical weather model.…”
Section: Introductionsupporting
confidence: 81%
“…Additionally, they stated that the agreement and the accuracy of the troposphere parameters mainly depend on the humidity in the atmosphere. Pollet et al (2014) also found that the consistency of ZTD parameters depends on the humidity level and the number of observations per estimated ZTD parameter. Heinkelmann et al (2016) compared the atmospheric parameters derived by DORIS, GPS, VLBI, and numerical weather models at five colocated sites during CONT14.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…In their geographical positions, the stations may be installed alone or co-located with other space geodetic techniques such as Very Long Baseline Interferometry (VLBI); Satellite Laser Ranging (SLR); Doppler Orbitography and Radiopositioning Integrated by Satellite (DORIS); water vapour radiometers (WVR) or tide gauge stations. In both single and multi-purpose CORS networks, ZTDs can be estimated from the tracked GNSS (Bevis et al, 1992;Alshawaf et al, 2017), VLBI (Heinkelmann et al, 2007;Balidakis et al, 2018); SLR (Pollet et al, 2014); DORIS (Teke et al, 2013), and WVR (Bock et al, 2010) observations.…”
Section: Introductionmentioning
confidence: 99%
“…A strong correlation exists between atmospheric parameters, especially Zenith Tropospheric Delays (ZTD), and the height component (Schuh and Behrend, 2012). Therefore, an improvement in the ZTD estimation can theoretically improve the co-located station positions (Pollet et al, 2014). Thus, the atmospheric parameters at the same observing site (atmospheric ties) could improve the combination of space geodetic techniques to establish an ITRF meeting the GGOS goals (Plag et al, 2009;Männel et al, 2019).…”
Section: Introductionmentioning
confidence: 99%